Low phosphatase activity of LiaS and strong LiaR-DNA affinity explain the unusual LiaS to LiaR in vivo stoichiometry - Jani, Shailee (BMC Microbiol, 2020)
BACKGROUND: LiaRS mediates Bacillus subtilis response to cell envelope perturbations. A third protein, LiaF, has an inhibitory role over LiaRS in the absence of stimulus. Together, LiaF and LiaRS form a three-component system characterized by an unusual stoichiometry, a 4:1 ratio between LiaS and LiaR, the significance of which in the signal transduction mechanism of LiaRS is not entirely understood. RESULTS: We measured, for the first time, the kinetics of the phosphorylation-dependent processes of LiaRS, the DNA-binding affinity of LiaR, and characterized the effect of phosphorylation on LiaR oligomerization state. Our study reveals that LiaS is less proficient as a phosphatase. Consequently, unspecific phosphorylation of LiaR by acetyl phosphate may be significant in vivo. This drawback is exacerbated by the strong interaction between LiaR and its own promoter, as it can drive LiaRS into losing grip over its own control in the absence of stimuli. These intrinsic, seemingly ‘disadvantageous”, attributes of LiaRS are likely overcome by the higher concentration of LiaS over LiaR in vivo, and a pro-phosphatase role of LiaF. CONCLUSIONS: Overall, our study shows that despite the conservative nature of two-component systems, they are, ultimately, tailored to meet specific cell needs by modulating the dynamics of interactions among their components and the kinetics of phosphorylation-mediated processes.